Singing with light: an interdisciplinary study on the medieval Ajuda Songbook. Issue 2 (2nd July 2016) - Nabais, Paula; Castro, Rita; Lopes, Graça Videira; de Sousa, Luís Correia; Melo, Maria João
ABSTRACT: A monument to Galician-Portuguese medieval lyric, the Ajuda Songbook ( Cancioneiro da Ajuda ) also contains an exceptional series of illuminations. Employing a multidisciplinary approach, this article uncovers the composition of the colour paints used in the Songbook, providing further insight into the circumstances of its production. It also connects the materiality of this manuscript to its economic and cultural context. Our determination of its molecular palette – and the identification of both orpiment and mosaic gold in particular – supports the argument put forward by scholars of medieval literature that the Songbook dates to the end of the thirteenth or beginning of the fourteenth century. We also highlight the extraordinary state of conservation of the lapis lazuli paint, and the presence of a pink colour made from brazilwood – the first reported use of this pigment in medieval manuscript illumination. Finally, we discuss the iconography of the Songbook's musical scenes with an emphasis on the depicted instruments. We consider these illuminations and the texts they accompany within their Iberian context (especially in relation to the Cantigas de Santa Maria ) and offer a brief comparison with those found in contemporary Occitan and French songbooks.